Characteristics of uterine myoma patients at inpatient rooms of dr. Soepraon 2nd Grade Military Hospital, Malang - Reny Retnaningsih; Zainal Alim (Universitas Airlangga, 2020)
Objectives: The aim of this study was to discover the characteristics of uterine myoma patients at the inpatient rooms of dr. Soepraon 2nd Grade Military Hospital, Malang.Case Report: Women reproductive system is prone to health problems, one of them is uterine myoma which being detected through pathology anatomy examination and shows an increasing prevalence (70%) nowadays. In Indonesia, the cases of uterine myoma reach 2,39 – 11,7%, placing second right after cervical cancer. The aim of this study was to discover the characteristics of uterine myoma patients at the inpatient rooms of dr. Soepraon 2nd Grade Military Hospital, Malang. The research design used in this study was case report. Population of this study included uterine myoma patients who were being treated at the inpatient rooms of dr. Soepraon 2nd Grade Military Hospital, Malang in between the period of January – December 2017 with a total of 82 patients. The sampling method used was total sampling. Sample of this study was acquired through secondary data in the form of medical records. The result of this study showed that the highest number of case was in the 50 – 54 years old age group (53.3%), the most common education background was high school graduates (46%), the most common occupation group was the unemployed (59%), the most common surgical therapy done was myomectomy (89%), the most common myoma was submucous myoma (46,3%) and the most common parity status was multipara (44%).Conclusion: Women aged 45 and older with multipara history are advised to maintain their reproductive health through healthy eating pattern, regular exercise and regular check-ups to detect the possibility of developing uterine myomas early.